As percepções de acadêmicas formandas do curso de pedagogia sobre alfabetização e letramento nos anos iniciais - Lemos, Helen Denise Daneres (2006)
This work focuses on teacher initial formation and highlights the final stage of the Pedagogy course, called Supervised Training. It is connected to the Research Line Teacher Education Qualification and Professional Development from the Post Graduation Program in Education at the Federal University of Santa Maria. Its main objective is to investigate the perceptions and the relationship among personal experiences, initial formation and educative practices of last year students from the Pedagogy Course regarding early literacy. From a qualitative approach based on Bogdan and Biklen (1994), the Life Story methodology for biography was applied to two last year academics. They presented oral and written reports, and were interviewed about their life experience. Research about initial and continuous teacher qualification, which values their personal and professional perspective is relevant for representing this yet little investigated dimension and answering questions concerning the initial qualification processes of literacy teachers, such as: What is the relationship established by the students on probatory training between their family and school memories and the educative practices they have applied while on training? What is the relationship between their own early education e those practices? How are their personal self and professional self articulated in the process of becoming a literacy teacher? How did the students articulate their life experience and qualification about literacy? Were they prepared to be literacy teachers? Did they realize their literate skills while teaching? Among the authors witch founded with their reflections in the writing this work were detached Contreras (2002), Nóvoa (1992, 2001, 2003), Antunes (1997, 2001, 2004), Bosi (1994), Soares (1997, 1998, 1999), Paiva (2005), Weiss (2004), Leão (2004, 2005). Final aspects point out the relevance of Life Stories for the reflection processes and consequent qualification of the students on training. They also point out how the relationship between the three levels (personal experiences, initial formation and educative practices) is built when focused a more personal perspective based on the student s own experiences. Other relationships involve a more social-historical approach, which similarly is influenced and influences the academics life stories. Thus, results show this study s relevance for the research field for allowing a contribution for the continuing improvement of the discussion on teacher initial formation, as well as for giving deserving attention to the final period of the degree in Pedagogy, which is the Supervised Training.